Reassessing an inferred Iroquoian village removal sequence in the Mohawk River Basin, New York, USA - J. P. Hart (Journal of Anthropological Archaeology, 2020)
All archaeologists use suppositions in their narratives to bridge gaps in empirical knowledge. If these suppositions are reasonable, they often become parts of regional archaeological traditions. However, such suppositions must be testable as new methods and techniques create new empirical evidence. In ancestral Mohawk Iroquoian archaeology, three village sites in the Caroga Creek drainage, thought to date to the sixteenth-century AD, have been accepted as a chronological sequence of villages occupied by the same community over the course of several generations. As reported here, however, social network analysis based on pottery collar design motifs demonstrates it is unlikely the sites represent such a sequence.
Keywords: Iroquoian archaeology; Mohawk River valley; Social network analysis; Village removal sequences